The impact of Oncotype DX testing on breast cancer management and chemotherapy prescribing patterns in a tertiary referral centre - McVeigh, Terri Patricia (Elsevier Science Ltd, 2014)
INTRODUCTION: The use of chemotherapy in node-negative, (O)Estrogen Receptor (ER)-positive breast cancer has changed significantly since the introduction of Oncotype DX to determine systemic recurrence risk based on tumour genomic signature. AIMS: This study aims to: 1. Document longitudinal changes in chemotherapy use, 2. Assess the impact of new evidence on local protocol. METHODS: A cohort study was undertaken, including consecutive patients with early node-negative, ER-positive breast cancer diagnosed between 2006 and May 2013, including a period of prospective clinical trial (Trial Assigning Individualised Options for Treatment (TAILORx)) recruitment. Data were collected regarding patient demographics, tumour clinico-pathological features, Oncotype DX use and recurrence score and chemotherapy use. All therapeutic decisions were made following multidisciplinary discussion, with adherence to guidelines and consideration of trial protocol and Oncotype DX recurrence scores. RESULTS: 479 consecutive patients were included in the study, of whom 241 (50%) underwent Oncotype DX testing, 97 as part of the TAILORx clinical trial. Oncotype DX testing began on a trial basis in 2007 and until October 2011, only patients enrolled on TAILORx availed of genomic profiling. From October 2011, Oncotype DX was used in all eligible patients as per National Cancer Control Programme (NCCP) guidelines. A total of 216 (45%) patients received chemotherapy. The use of chemotherapy changed in inverse proportion to the availability of the genomic assay. Of those patients in whom Oncotype DX was utilised, 138 (57%) were spared chemotherapy. CONCLUSION: This study validates the use of molecular testing in the rationalisation of systemic therapy.